2001
DOI: 10.1021/ja017365j
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Writing of Polymer Nanostructures:  Poly(thiophene) Nanowires on Semiconducting and Insulating Surfaces

Abstract: A new technique for direct-writing of polymer nanostructures on insulating and semiconducting surfaces based on Electrochemical Dip-Pen Nanolithography (E-DPN) is described. The technique is based on electrochemical polymerization of monomers directly underneath the AFM tip. Sub-50 nm poly-3,4-ethylenedioxythiophene lines can be easily created. Such capability to direct-write and pattern polymeric materials with interesting electronic and electrooptical properties at the nanoscale creates a number of opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
236
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 317 publications
(243 citation statements)
references
References 21 publications
0
236
1
3
Order By: Relevance
“…8). Maynor et al (2002) reported the PEDOT line deposition on an anodic silicon surface simultaneous with oxidation. Fig.…”
Section: Dip-pen Nanolithographymentioning
confidence: 99%
“…8). Maynor et al (2002) reported the PEDOT line deposition on an anodic silicon surface simultaneous with oxidation. Fig.…”
Section: Dip-pen Nanolithographymentioning
confidence: 99%
“…Nanometer sized deposits can be achieved mainly by nanolithographic approaches. Next to surface probe microscopy techniques, for example dip-pen nanolithography (DPN), electrochemical DPN, electrostatic nanolithography, and electron beam lithography [236][237][238][239], nanolithography based on C-AFM has been extensively used for nanopatterning of monomer and precursor polymer films [240][241][242][243][244], in contrast with DPN and electrostatic nanolithography, in which monomer inks or electrolyte-saturated films are used [236,237,241]. C-AFM enables direct preparation of polymer films by electrochemical means on spin-cast monomers under ambient temperature and humidity conditions.…”
Section: Osmentioning
confidence: 99%
“…For one-dimensional nanostructures, CP nanowires and nanofibres have been prepared by a variety of methods, including dip-pen nanolithography (DPN) [113][114][115], electrospinning [116][117][118], template-assisted synthesis [119], soft template, vapour transport and deposition [120], and solution-phase self-assembly [121][122][123][124]. Controlling the dimensions (diameter or width d, length L) of nanowires is a key issue in the development of advanced materials.…”
Section: Introductionmentioning
confidence: 99%